COMPARATIVE COST-MINIMIZATION AND BUDGET-IMPACT ANALYSIS OF FIXED-DOSE INHALED CORTICOSTEROID / LONG-ACTING BETAAGONIST COMBINATIONS IN THE TREATMENT OF ASTHMA - N. L. Pogudina; E. G. Kosolapov; F. S. Kochenkov; A. V. Karaulov; N. L. Bondarenko; D. V. Blinov (IRBIS LLC, 2017)
Comparative pharmacoeconomic analysis of fixed-dose combinations (FDC) vilanterol / fluticasone furoate vs budesonide / formoterol was needed to identify the preferable FDC for asthma management.Study objective: to identify the preferable FDC of inhaled corticosteroid/ longacting beta agonist combinations (ICS/LABA) for the treatment of moderate or severe asthma in Russia. Materials andMethods. Retrospective comparative pharmacoeconomic study; cost-minimization analysis and budget-impact analysis.Results. The present analysis shows that the 12-month direct medical costs for the treatment of asthma using vilanterol / fluticasone furoate and budesonide / formoterol are 29,276 and 40,447 RUR per patient, respectively. The direct costs of treatment with vilanterol / fluticasone furoate are less than those for budesonide / formoterol by 28%. The annual health budget savings that result from replacing budesonide / formoterol by vilanterol / fluticasone furoate are 1,151,512,731 RUR per 100,000 patients.Conclusion. The present results indicate that the vilanterol / fluticasone furoate FDC is preferable (more beneficial) as compared with the budesonide / formoterol FDC.